2019
DOI: 10.3389/fpls.2019.00876
|View full text |Cite
|
Sign up to set email alerts
|

Density-Dependent Plant–Plant Interactions Triggered by Grazing

Abstract: Plant species performance in rangelands highly depends on the effect of grazing and also on the occurrence of unpalatable benefactor species that can act as biotic refuges protecting neighboring plants from herbivores. The balance between facilitation and competition may changes with the benefactor density. Despite the high number of studies on the role of biotic refuges, the density dependent effects of unpalatable herbaceous plants on the performance of other species, and on the habitat heterogeneity of rang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 51 publications
1
4
0
Order By: Relevance
“…Sheep preferentially forage palatable and nutritious species, which indirectly increases the dominance of the community by reducing competition from other species (increasing the dominance of S. grandis) (Liang et al, 2019). Some studies suggest that unpalatable species act as biological refuges by protecting neighboring plants from being eaten (Smith et al, 2009;Kelemen et al, 2019). Our research confirmed this, as high grazing intensity significantly promoted an increase in species richness by increasing the dominance of the community.…”
Section: Grazing Affect Plant Diversitysupporting
confidence: 82%
“…Sheep preferentially forage palatable and nutritious species, which indirectly increases the dominance of the community by reducing competition from other species (increasing the dominance of S. grandis) (Liang et al, 2019). Some studies suggest that unpalatable species act as biological refuges by protecting neighboring plants from being eaten (Smith et al, 2009;Kelemen et al, 2019). Our research confirmed this, as high grazing intensity significantly promoted an increase in species richness by increasing the dominance of the community.…”
Section: Grazing Affect Plant Diversitysupporting
confidence: 82%
“…Second, plateau pikas prefer graminoids as food throughout their home range ( Liu et al, 2017 ), which alters the existing interspecific and intraspecific relationships among plants because graminoids are often dominant plants ( Pang and Guo, 2018 ). This usually divides the areas with plateau pikas into alpine meadows dominated by strongly competitive dominant species and other alpine meadows dominated by disturbance-dependent species ( Yoshihara et al, 2009 ; Kelemen et al, 2019 ), contributing to an increase in spatial heterogeneity of vegetation. Third, the presence of plateau pikas is beneficial to seed dispersal ( Dobson et al, 1998 ).…”
Section: Discussionmentioning
confidence: 99%
“…The facilitative effect of dominant perennials (including, in our case, Sporobolus ) mostly occurs through the facilitation of the germination and early establishment of subordinate species, but this positive interaction can turn into competition for light or space (Liancourt et al 2005, Le Roux et al 2013). The sign of the interaction between plant species is also density-dependent; a low density of a facilitator species can have positive effects, but it can turn to negative interaction above a certain density of the species (Kelemen et al 2019). This is in line with our findings as the richness and abundance of subordinated species in the vegetation and seed banks was higher in plots with a low density of Sporobolus than in plots without Sporobolus, but a higher density of the species had an overall negative effect.…”
Section: Discussionmentioning
confidence: 99%